Analysis of growth and development levels and influencing factors in children aged 3–12 years in a certain region: a cross-sectional study - Gong, Liping; Song, Yufeng; Cheng, Shengquan; Du, Jing; Liang, Juan (Frontiers in Public Health, 2025)
ObjectiveThis multi-center cross-sectional study aims to analyze growth and development levels and identify factors influencing these parameters among children aged 3–12 years in multiple regions of China.MethodsA total of 4,219 children (2,231 males and 1988 females) were included from local schools and community centers across 10 regions. Physical measurements (height, weight, and BMI) and bone age (assessed by R-series and C-series methods) were recorded. Parental heights were used to predict genetic adult height. A structured questionnaire provided data on demographics, family medical history, and lifestyle factors. Statistical analyses included t-tests, Pearson’s correlation, and multiple linear regression.ResultsNo significant sex differences were found in growth and development indices across age groups. Predicted adult height was higher in boys (176.17 ± 104.77 cm) than in girls (169.06 ± 7.13 cm). Age showed positive correlations with height (r = 0.400, p < 0.001), weight (r = 0.584, p < 0.001), and BMI (r = 0.699, p < 0.001). Father’s height was positively correlated with child height (r = 0.106, p = 0.041). Multiple linear regression indicated that age, weight, BMI, father’s height, and C-series bone age were significant predictors of child height (p < 0.001), with weight having the largest effect (β = 1.012). BMI and C-series bone age were significant predictors of weight (p < 0.001), while weight and height were significant predictors of BMI (p < 0.001).ConclusionGrowth and development in children are influenced by a combination of genetic, nutritional, and environmental factors. Understanding these influences can aid in developing targeted interventions to promote healthy growth patterns among children across diverse regions.